Manfaat Learning Resources dalam Pembelajaran Student Centered Learning : Manfaat Learning Resources dalam Pembelajaran Student Centered Learning - Untung suryadhianto; Haris Mujianto (ZETROEM, 2020)
This research to provide a description of the SCL learning process by utilizing information technology internet media with research library methods which is a method of searching, collecting and analyzing data sources to be processed and presented in the form of a report.The existence of information technology is a rapid progress in supporting the world of education as an economical, practical, and easy learning resource. Student Centered Learning (SCL) is learning that is in accordance with the current digital era, so that the role of lecturers in the learning and learning process is as a companion, motivator and facilitator. The activeness of students in the learning and learning process is an important factor, because with the direct involvement of students, the lecture material is easy to understand and understand.